Dinasti Mamalik di Mesir - Darmalaksana, Wahyudin (el Harakah: Jurnal Budaya Islam, 2009)
This paper intends to explore the historical aspect of Mamalik dynasty. It was associated with Daulah Islamiyah in Mesir which lead by slave group (Mamalik) from 13th century up to 16th A.D that became one of unique Islamic political faces. At that time, civil society can form themselves as military power driven by slavers. Retired slavers emerged as political elite and bodyguard of Sultan. Mamalik group divided into two groups. First, Mamalik Bahriyah coming from middle Asia, especially Turkey Qipsaq. Second, Mamalik Burjiyah coming from Sirkasia race in·Kaukasus (East Europe). Historically, Mamalik Dynasty in Mesir classified into three periods. First, the period of Mamalik government formation which was "oligarchy". Second, the period of development in which Mamalik group cooperated with Mogol and Europe country. Third, the period of saturation or the decrease of Mamalik dynasty in Mesir which was caused by the attack of Turkey Utsmani, disease epidemic, and corruption. Makalah ini bermaksud untuk mengeksplorasi aspek historis dinasti Mamalik. Itu terkait dengan Daulah Islamiyah di Mesir yang dipimpin oleh kelompok budak (Mamalik) dari abad ke-13 hingga 16. yang menjadi salah satu wajah politik Islam yang unik. Saat itu, masyarakat dapat membentuk diri mereka sebagai kekuatan militer yang dikendalikan oleh budak. Mantan budak muncul sebagai elit politik dan pengawal Sultan. Kelompok Mamalik dibagi menjadi dua kelompok. Pertama, Mamalik Bahriyah yang berasal dari Asia tengah, terutama Turki Qipsaq. Kedua, Mamalik Burjiyah berasal dari ras Sirkasia di Kaukasia (Timur Eropa). Secara historis, Dinasti Mamalik di Mesir digolongkan ke dalam tiga periode. Pertama, periode pembentukan pemerintahan Mamalik yang merupakan "oligarki". Kedua, periode perkembangan di mana Kelompok Mamalik bekerja sama dengan Mongolia dan negara Eropa. Ketiga, periode kejenuhan atau penurunan dinasti Mamalik di Mesir yang disebabkan oleh serangan Turki Utsmani, epidemi penyakit, dan korupsi.